Ordem e subversão nas cidades: um estudo sobre a população em situação de rua de Belo Horizonte - Bruno Eduardo Freitas Honorato (2014)
My initial objective of this study was to characterize the social practices of the homeless in relation to the policy of social actions in the city of Belo Horizonte. In the case of the homeless population, policies for social action featuring the creators of the organizations to which it relates sources and social practices, modes of action, before these organizations. Whereas, homeless undertake various relationships with these organizations, the main aim of this study was to observe the relationship construction of a social arder within and outside these organizations, and how homeless dealing with this arder, giving views, especially the subversive practices that are seen as movements of direct and indirect opposition to this arder . The arder as a concept is understood in this study as a possible organi zation, planned andexecuted according to criteria of some social group, or an individual within a system defined to justify or attempt to justify rationally their existence. The arder, considered as a concept, defines a confined space and "consumption" (Certeau , 1998, p. 16 ) that can be dane in thisspace. Defining rules of movement and possibilities of earnings for each involved part. While the subversion features circumvention practices that arder. The term subversion can be understood as a reaction to a set of voices to planning and controlling operations of the dominant structure (CARRIERI et al. 2008) taking as basis the subversion operates andmaintains the conflict. Subvert isto use an i Ilegal or informal, of what is expected to be dane. This ability to act in violation of the dictates of a particular organized system is based on repossessions that individuais make the rules and laws laid down by different uses (Certeau, 1998 ) of something that was supposed to be received passively . What is stressed from the beginning, as the central argument of this work is the idea that , not because the homeless receive shelter and food for others , they necessarily will undergo a system that , somehow , imprisons them in an arder that they do not recognize as legitimate. Therefore, the theme of subversion was relevant in the study ofthe relationships between population undettaken in the streets and organizations. The town, as the stage of conflict and investigative locus of this research is also of fundamental importance as a source of information to build knowledgeabout this relationship. Understand the city is also to understand the rules that shape the spaces and boundaries of each of its actors, the possibilities of use and the extensions of their physical layout . The city is platmed and configured for human use, composing one of the organizations in which we place ourselves in everyday life. (MAC ALLISTER, 2001 ; 2004; HATL ; CARRTERI 2012) . The consequences of a study of the city of Belo Horizonte as an organization invo lve understanding the range of social and spatial phenomena acting together in building a culture that identifies the subjects that fall within it. Therefore, the behaviors of the homeless were observed in relation to arder and subversion or strategies and tactics (de Cetteau, 1 998) , and aspects that relate to this theme in the town and care facilities to thepeople living on the streets ofBelo horizon. The evidence found strengthens the argument that it is not a complete organizational contra! o ver the practices of these people, even i f they are subjected to various forms o f dependence o f the various organizations that are assisti v e aid.